1997
DOI: 10.1139/z97-050
|View full text |Cite
|
Sign up to set email alerts
|

Thermal environment for overwintering hatchlings of the painted turtle (Chrysemys picta)

Abstract: We monitored temperatures during the winter of 1995–1996 inside 18 nests containing hatchling painted turtles (Chrysemys picta). The study was performed at the Valentine National Wildlife Refuge in north-central Nebraska to assess survival of neonatal turtles in relation to the thermal environment inside their hibernacula. Minimum temperatures in the nests varied from −3 to −21 °C, and were better predictors of survival of hatchlings than other measures of the thermal environment. All hatchlings survived in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 13 publications
1
34
0
Order By: Relevance
“…It is not known how C. longicollis and E. macquarii accelerate development, but heart rates are not fixed and environmental conditions merely determine the limits of heart rate and thus developmental rate (McGlashan et al, 2012;Loudon et al, 2013). Synchronous hatching has evolved in many aquatic turtles with many abiotic and biotic factors serving as the cues (Webb et al, 1986;Thompson, 1989;Lindeman, 1991;Packard et al, 1997;Doody et al, 2001;Spencer et al, 2001;Packard and Packard, 2004;Tucker et al, 2008;Colbert et al, 2010;Spencer and Janzen, 2011). Synchronous hatching is not a passive action, it is driven by embryo-embryo communication in the nest.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known how C. longicollis and E. macquarii accelerate development, but heart rates are not fixed and environmental conditions merely determine the limits of heart rate and thus developmental rate (McGlashan et al, 2012;Loudon et al, 2013). Synchronous hatching has evolved in many aquatic turtles with many abiotic and biotic factors serving as the cues (Webb et al, 1986;Thompson, 1989;Lindeman, 1991;Packard et al, 1997;Doody et al, 2001;Spencer et al, 2001;Packard and Packard, 2004;Tucker et al, 2008;Colbert et al, 2010;Spencer and Janzen, 2011). Synchronous hatching is not a passive action, it is driven by embryo-embryo communication in the nest.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable ability of hatchling C. picta to tolerate subzero temperatures (to -11°C in natural nests : Woolverton 1963;Costanzo et al 1995;Packard 1997;Packard et al 1997) has been suggested as a factor promoting the species' extreme northern distribution (Paukstis et al 1989;St. Clair and Gregory 1990).…”
Section: Discussionmentioning
confidence: 99%
“…As winter approaches and nest temperatures fall, hatchlings become more cold hardy and are able to survive modest subzero exposures either by freezing or by remaining supercooled (Costanzo et al 1998). However, nest temperatures in winter can fluctuate substantially, including abrupt decreases (i.e., 0Њ to Ϫ13ЊC in ∼24 h; Packard et al 1997), and in the northern part of the painted turtle's range can be less than Ϫ15ЊC (Costanzo et al 2008). Having the capacity to rapidly enhance cold hardiness during the more extreme temperature fluctuations would seemingly lessen winter mortality.…”
Section: Introductionmentioning
confidence: 99%